2020
DOI: 10.3389/fnmol.2020.00078
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of RNA-Binding Proteins in Amyotrophic Lateral Sclerosis

Abstract: Genetic analyses of patients with amyotrophic lateral sclerosis (ALS) have revealed a strong association between mutations in genes encoding many RNA-binding proteins (RBPs), including TARDBP, FUS, hnRNPA1, hnRNPA2B1, MATR3, ATXN2, TAF15, TIA-1, and EWSR1, and disease onset/progression. RBPs are a group of evolutionally conserved proteins that participate in multiple steps of RNA metabolism, including splicing, polyadenylation, mRNA stability, localization, and translation. Dysregulation of RBPs, as a conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 123 publications
3
59
0
1
Order By: Relevance
“…FUS can be post-translationally modified at various positions, leading to modification of its cellular localization, aggregation, and self-assembly tendency. Phosphorylation, acetylation, glycosylation, mono- and di-methylation, and ubiquitination have been described to occur at different positions along FUS protein (for extensive reviews, see [ 223 , 224 ]). Interestingly, FUS phosphorylation seems very labile in Drosophila , and hypophosphorylated forms of the protein alter FUS solubility properties, causing toxicity.…”
Section: Fus An Rna-binding Protein Associated With Alsmentioning
confidence: 99%
“…FUS can be post-translationally modified at various positions, leading to modification of its cellular localization, aggregation, and self-assembly tendency. Phosphorylation, acetylation, glycosylation, mono- and di-methylation, and ubiquitination have been described to occur at different positions along FUS protein (for extensive reviews, see [ 223 , 224 ]). Interestingly, FUS phosphorylation seems very labile in Drosophila , and hypophosphorylated forms of the protein alter FUS solubility properties, causing toxicity.…”
Section: Fus An Rna-binding Protein Associated With Alsmentioning
confidence: 99%
“…Sporadic forms of the disease are the most abundant (Al‐Chalabi & Hardiman, 2013). However, these forms are clinically and histopathologically indistinguishable from the different familial forms described so far, which involve mutations in genes such as (i) SOD1 encoding the key anti‐oxidant enzyme superoxide dismutase (SOD1) (Kaur et al, 2016); (ii) TARDBP and FUS encoding the proteins TAR‐DNA binding protein‐43 (TDP‐43) or fused in sarcoma (FUS), involved in pre‐mRNA splicing, transport and stability (Butti & Patten, 2019; Xue et al, 2020) and (iii) C9ORF72 encoding a protein involved in intracellular trafficking in neurons and other cell functions not completely understood (Gijselinck et al, 2018; Renton et al, 2011). These mutant genes ( SOD1 , TARDBP , FUS and C9orf72 ) represent, among more than 25 ALS‐related genes, in most of the cases of familial ALS (Al‐Chalabi & Hardiman, 2013; Gao et al, 2017; Kim et al, 2020), and they have been used to generate experimental models (transgenic mice overexpressing different human mutations) for the study of ALS (Van Damme et al, 2017).…”
Section: Cannabinoids and Alsmentioning
confidence: 99%
“…However, a definite environmental risk factor has not been clearly identified so far. Since the first identification of superoxide dismutase 1 ( SOD1 ) as an ALS causative gene in 1993 [ 7 ], significant research efforts and advanced genetic approaches have identified mutations in more than 30 genes that cause ALS and frontotemporal dementia (FTD) [ 15 , 16 , 17 , 18 ]. In addition, 147 different gene mutations found in many different pathways have been shown to contribute to the pathogenesis of ALS [ 19 , 20 ].…”
Section: Rna-binding Proteins and Alsmentioning
confidence: 99%
“…Mutations in a series of RNA-binding protein genes, TAR DNA binding protein ( TARDBP ), FUS RNA-binding protein ( FUS ), TATA-box binding protein associated factor 15 ( TAF15 ), EWS RNA-binding protein 1 ( EWSR1 ), heterogeneous nuclear ribonucleoprotein A1 ( HNRNPA1 ), HNRNPA2B1 , Ataxin 2 ( ATXN2 ), and TIA1 cytotoxic granule associated RNA-binding protein ( TIA1 ), have been shown to cause or influence the disease risk for ALS and/or FTD [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. ALS causative genes such as FUS and TARDBP encode RNA-binding proteins and lead to disrupted RNA metabolism [ 18 ]. ALS-causative mutations in FUS or TARDBP show abnormal stress granule formation with defects in translation, the formation of pathogenic RNA foci, the dysregulation of nucleocytoplasmic shuttling, as well as other forms of disrupted RNA metabolism [ 32 , 33 ].…”
Section: Rna-binding Proteins and Alsmentioning
confidence: 99%